PENGEMBANGAN APLIKASI ANDROID PADA SISTEM PENDETEKSI DINI KEBAKARAN LAHAN - Araminta, Nada; Wagyana, Agus (TESLA: Jurnal Teknik Elektro, 2021)
Land fires are a tragedy that is difficult to control if the fire is large and can result in considerable losses. To be able to reduce the impact of losses due to land fires, an early warning is needed, therefore an application system is made that can detect land fires based on fire, smoke and temperature parameters. The methods used in the process of making this application are application system planning, application feature planning, layout design and java programming for each feature using Android Studio, configuration and programming on firebase, and finally the application can be released. This application uses firebase as a database platform that will store sensor data, user data, and cloud functions. The way this application works is that the application will display data on land conditions in real time, and when there is a change in status, the firebase will execute a command to provide a fire status warning via push notification in the form of a "safe", "alert", "fire level 1" status, or “fire level 2” to the application so that landowners can act on them immediately. The quality of this application is assessed through testing based on the ISO/EIC 25010 standard, namely testing database accuracy, compatibility, usability, and performance efficiency aspects. With the test results of 100% database accuracy, 100% compatibility, and 86% usability, the application is categorized as very feasible and with 3,213% CPU usage efficiency and 159,213 KB memory that meets little eye standards, it shows that the "Siaga Api" application has very good qualit ABSTRAK: Kebakaran lahan merupakan tragedi yang sulit untuk dikendalikan jika api sudah besar dan dapat mengakibatkan kerugian yang cukup besar. Untuk dapat mengurangi dampak kerugian akibat kebakaran lahan, diperlukan adanya sebuah peringatan dini, maka dari itu dibuatlah sebuah sistem aplikasi yang dapat mendeteksi kebakaran lahan berdasarkan parameter api, asap dan suhu. Metode yang digunakan pada proses pembuatan aplikasi ini adalah perencanaan sistem aplikasi, perencanaan fitur aplikasi, perancangan layout serta pemrograman java untuk setiap fitur menggunakan Android Studio, konfigurasi dan pemrograman pada firebase, dan akhirnya aplikasi dapat di release. Aplikasi ini menggunakan firebase sebagai platform database yang akan menyimpan data sensor, data pengguna, serta cloud function. Cara kerja dari aplikasi ini adalah aplikasi akan menampilkan data kondisi lahan secara realtime, dan ketika terjadi perubahan status maka firebase akan mengeksekusi perintah untuk memberikan peringatan status kebakaran melalui push notification berupa status “aman”, “waspada”, “kebakaran level 1”, atau “kebakaran level 2” ke aplikasi sehingga pemilik lahan dapat langsung bertindak menanganinya. Kualitas aplikasi ini dinilai melalui pengujian yang berdasarkan standar ISO/EIC 25010 yaitu pengujian akurasi database, aspek compatibility, usability, dan performance efficiency. Dengan hasil uji akurasi database 100%, compatibility 100%, dan usability 86% aplikasi dikategorikan sangat layak serta dengan performance efficiency CPU usage 3,213% dan memory 159,213 KB yang memenuhi standar little eye menunjukkan bahwa aplikasi “Siaga Api” memiliki kualitas yang sangat baik.